Poly (methyl methacrylate)-grafted alginate/Fe3O4 nanocomposite: synthesis and its application for the removal of heavy metal ions. Issue 42 (7th September 2016) - Mittal, Alok; Ahmad, Rais; Hasan, Imran
Abstract: A novel adsorbent poly (methyl methacrylate)-grafted alginate/Fe3 O4 nanocomposite was synthesized by oxidative-free radical-graft copolymerization reaction. The nanocomposite was characterized using FT-IR, X-ray diffraction, SEM, TEM, TGA and DSC techniques. The potential of nanocomposite material was explored towards the adsorption of Pb(II) and Cu II) from aqueous media under varying operating conditions such as pH, concentration of metal ions, contact time, adsorbent dose and temperature. The optimum pH recorded for metal ions adsorption was 5. The experimental data were tested using Langmuir, Freundlich, Sips and Temkin models, and the data were best followed by Freundlich model at 50°C. The maximum sorption capacity was found to be 62.5 mg g −1 for Pb(II) and 35.71 mg g −1 for Cu(II), respectively. The concentration and temperature dependent rate constants were evaluated using various kinetic models, and the data were best followed by pseudo-second-order kinetic model. The thermodynamic parameters such as enthalpy, entropy and free energy of activation were calculated to explain the nature of adsorption process.